PEONIES: ACHIEVEMENTS OF RUSSIAN BREEDERS - L. N. Mironova; A. A. Reut (Вавиловский журнал генетики и селекции)
Achievements of Russian peony breeders are presented. The main breeding stages are considered. The results of 60-year peony breeding in the Botanical Garden of the Ufa Research Center are outlined. Hybrid peony varieties are characterized.